2011
DOI: 10.1016/j.lfs.2011.01.009
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Angiotensin receptor blockade improves the net balance of cardiac Ca2+ handling-related proteins in sympathetic hyperactivity-induced heart failure

Abstract: Altogether, these data provide new insights on intracellular Ca(2+) regulatory mechanisms underlying improved ventricular function by ARB therapy in HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
(44 reference statements)
4
16
0
Order By: Relevance
“…However, Losartan also induced an increase on cardiac SERCA2a gene expression. This observation is in agreement with a previous study, which demonstrated that the blockade of AT1R promoted an increase on cardiac SERCA2a levels [18].…”
Section: Discussionsupporting
confidence: 94%
“…However, Losartan also induced an increase on cardiac SERCA2a gene expression. This observation is in agreement with a previous study, which demonstrated that the blockade of AT1R promoted an increase on cardiac SERCA2a levels [18].…”
Section: Discussionsupporting
confidence: 94%
“…The change in the caffeine-induced Ca 2+ release curve was potentially due to Losartan increasing the expression of NCX [32], which is the sole channel responsible for clearing Ca 2+ from the cytosol during treatment with caffeine. It is, however, unlikely that Ca 2+ signaling is the entire mechanism of improvement following Losartan treatment as tumor-induced changes in the amplitude of the Ca 2+ transient are unaffected by Losartan.…”
Section: Discussionmentioning
confidence: 99%
“…Other angiotensin II related drugs, losartan (an ARB) and temocapril (an inhibitor of angiotensin converting enzyme), have been shown to have protective effects against both the abnormal amounts of PLB and SERCA and the LV dysfunction associated with sympathetic hyperactivityinduced heart failure and salt-induced hypertension (Satoh et al 2003;Ferreira et al 2011). Telmisartan has been previously shown (D) CF rate (CFR) was calculated by dividing CF by heart mass.…”
Section: Discussionmentioning
confidence: 99%